2021
DOI: 10.1177/02655322211049097
|View full text |Cite
|
Sign up to set email alerts
|

Gauging the impact of literacy and educational background on receptive vocabulary test scores

Abstract: The Peabody Picture Vocabulary Test (PPVT) is a widely used test of receptive vocabulary, but no researchers to date have examined the performance of low-educated, low-literate L2 adults, or compared these individuals’ performances to their more highly educated peers. In this study, we used many-facet Rasch analysis and mixed-effects linear regression to determine the impact of educational background and other demographic variables on PPVT test performance. The analyses rely on the performance data of 1014 adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…While the beneficial impact of L2 instruction on higher educated learners has been widely reported (Housen & Pierrard, 2005;Loewen, 2018), little or no research has examined the L2 gains of adults who have had reduced access to formal education and who are not functionally literate in an alphabetic script (Deygers & Vanbuel, 2021;Ortega, 2005;Rüsseler et al, 2021;Tarone, 2010). Throughout this paper, we will use the acronym LESLLA to refer to adult L2 learners with a history of (functional) illiteracy and reduced educational access (Carlsen, 2017;Deygers & Vanbuel, 2021;Huettig, 2015). We define reduced educational access as not having had the opportunity to attend formal education for more than nine years (European Commission/EACEA/Eurydice, 2015; Vagvoelgyi et al, 2016).…”
Section: Instructed Sla and Adult L2 Tracksmentioning
confidence: 99%
See 1 more Smart Citation
“…While the beneficial impact of L2 instruction on higher educated learners has been widely reported (Housen & Pierrard, 2005;Loewen, 2018), little or no research has examined the L2 gains of adults who have had reduced access to formal education and who are not functionally literate in an alphabetic script (Deygers & Vanbuel, 2021;Ortega, 2005;Rüsseler et al, 2021;Tarone, 2010). Throughout this paper, we will use the acronym LESLLA to refer to adult L2 learners with a history of (functional) illiteracy and reduced educational access (Carlsen, 2017;Deygers & Vanbuel, 2021;Huettig, 2015). We define reduced educational access as not having had the opportunity to attend formal education for more than nine years (European Commission/EACEA/Eurydice, 2015; Vagvoelgyi et al, 2016).…”
Section: Instructed Sla and Adult L2 Tracksmentioning
confidence: 99%
“…There are good reasons to assume, however, that the type of L2 track does impact gains. In a study on receptive vocabulary gains, Deygers & Vanbuel (2021) found that track type was a significant predictor of receptive vocabulary scores on a standardized test (the Dutch version of the Peabody Picture-Vocabulary Test, the PPVT-III-NL, see Dunn et al, 2005), after controlling for individual learner characteristics.…”
Section: Instructed Sla and Adult L2 Tracksmentioning
confidence: 99%